Beyond the founders : new approaches to the political history of the early American republic - Pasley, Jeffrey L., 1964-; Robertson, Andrew W. (Andrew Whitmore), 1951-; Waldstreicher, David (University of North Carolina Press, 2004)
In pursuit of more sophisticated and inclusive American history, the contributors propose new directions for the study of the political history of the republic before 1830. This political world encompassed blacks, women, entrepreneurs, and Native Americans. The early history of the United States was not just the product of the "founding fathers."